1963
DOI: 10.1126/science.142.3598.1479
|View full text |Cite
|
Sign up to set email alerts
|

Serum Factor in Renal Compensatory Hyperplasia

Abstract: Serum from uninephrectomized rats was injected into normal recipient rats. This led to an increased incorporation of tritiated thymidine in the kidney cells, but not in the liver cells of the recipients. The results suggest that there is a humoral substance acting specifically on the kidney that promotes renal compensatory hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1966
1966
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 5 publications
0
34
0
2
Order By: Relevance
“…Many diverse type experiments and assays suggest the presence of a circulating renotropic factor [8,11,[13][14][15][16][17][18]20]. Some investigators have injected test sera into living animals and estimated DNA synthesis by the incorporation of :IH-Tdr into DNA [10,19] or added test sera to tissue cultures and measured the mitotic index [13]. In 1970, we found that sera removed from UNI rats enhance :1H-Tdr monophosphate incorporation into DNA [18], Over the following years, using a similar in vitro assay system, we described a renotropic system in rats [16].…”
Section: Discussionmentioning
confidence: 99%
“…Many diverse type experiments and assays suggest the presence of a circulating renotropic factor [8,11,[13][14][15][16][17][18]20]. Some investigators have injected test sera into living animals and estimated DNA synthesis by the incorporation of :IH-Tdr into DNA [10,19] or added test sera to tissue cultures and measured the mitotic index [13]. In 1970, we found that sera removed from UNI rats enhance :1H-Tdr monophosphate incorporation into DNA [18], Over the following years, using a similar in vitro assay system, we described a renotropic system in rats [16].…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION Existence of circulating renotropins, factors affecting some aspect of renal cellular growth, is supported by the ability of sera from UNI animals to enhance isotopic labeling of nucleic acids in renal tissue cultures and intact kidneys (10)(11)(12)(13)(14)(15)(16). In 1970, we utilized an in vitro assay to detect a circulating renotropin that stimulates DNA synthesis as measured by isotopic labeling of DNA in rat kidney slices (3).…”
mentioning
confidence: 99%
“…There have been numerous reports of circulating or humoral factors which alter renal RNA and/or DNA metabolism [6,11,12,17,20], Factors that both stimulate [11,12] and inhibit [20] biochemical growth have been described. Increased RNA and/or DNA accumulation would, thus, result from in creased levels of renal responsiveness to a stimulating factor or from decreased levels of renal responsiveness to an inhibiting fac tor.…”
Section: Discussionmentioning
confidence: 99%
“…and (2) What is the relationship between the biochemical (RNA and DNA) and the physiological (RBF and GFR) changes? While numerous experimentals manipulations and plasma or urine factors have been shown to alter renal RNA, DNA and/or protein metabolism [6,11,12,17,20], the absence of information on the effects of these on renal function precludes definitive conclusions being made with re gard to the overall 'growth' response. Thus resolution of the second question is requisite to elucidation of possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%